Making International Organizations More Democratic - Alois Stutzer; Bruno S. Frey (Center for Research in Economics, Management and the Arts (CREMA), 2004)
World governance today is characterized by international organizations lacking democratic legitimacy and control by the citizens they claim to represent. They are also criticized for being inefficient. This leads to violent protests and to NGOs having great influence. To address these problems, we propose international governance based on the democratic idea of citizen participation: All citizens of the member countries of international organizations have the potential right to participate in the decision-making of international organizations via initiatives, referendums and recalls. In order to reduce transaction costs, a representative group of citizens is randomly selected who can actually exercise their participation rights.
Keywords: D72; O19; 330; international organizations; initiative; random selection; recall; referendum